Famous Pitch Lake, La Brea, Trinidad - (:unkn) unknown (My University, 2009)
Photo of employees at the La Brea, Pitch Lake in Trinidad. No.35
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Employees--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Pitch Lake, The (La Brea)